Epigenetic memory in the context of nuclear reprogramming and cancer - Halley-Stott, Richard P. (Oxford University Press, 2013)
Epigenetic memory represents a natural mechanism whereby the identity of a cell is maintained through successive cell cycles, allowing the specification and maintenance of differentiation during development and in adult cells. Cancer is a loss or reversal of the stable differentiated state of adult cells and may be mediated in part by epigenetic changes. The identity of somatic cells can also be reversed experimentally by nuclear reprogramming. Nuclear reprogramming experiments reveal the mechanisms required to activate embryonic gene expression in adult cells and thus provide insight into the reversal of epigenetic memory. In this article, we will introduce epigenetic memory and the mechanisms by which it may operate. We limit our discussion primarily to the context of nuclear reprogramming and briefly discuss the relevance of memory and reprogramming to cancer biology.